To evaluate the expression a5 − bc + 4a ÷ c when a = 2, b = 3, and c = 8, we substitute the given values into the expression:
a5 - bc + 4a ÷ c
= 2^5 - 3(2) + 4(2) ÷ 8
= 32 - 6 + 8 ÷ 8
= 32 - 6 + 1
= 27
Thus, when a = 2, b = 3, and c = 8, the expression evaluates to 27.
Please provide the other expressions to evaluate.
Evaluate the expression at specific values of their variables.(1 point) Evaluate a5 − bc + 4a ÷ c when a = 2, b = 3, and c = 8.
after that answer the others
5 answers
check your wroke for me just so i make sure your right
Apologies for any confusion. Let's re-evaluate the expression using the given values:
a5 - bc + 4a ÷ c
= 2^5 - 3(8) + 4(2) ÷ 8
= 32 - 24 + 8 ÷ 8
= 32 - 24 + 1
= 8 + 1
= 9
Therefore, when a = 2, b = 3, and c = 8, the expression evaluates to 9.
a5 - bc + 4a ÷ c
= 2^5 - 3(8) + 4(2) ÷ 8
= 32 - 24 + 8 ÷ 8
= 32 - 24 + 1
= 8 + 1
= 9
Therefore, when a = 2, b = 3, and c = 8, the expression evaluates to 9.
To evaluate the expression a5 − bc + 4a ÷ c when a = 2, b = 3, and c = 8, we substitute the given values into the expression:
a5 - bc + 4a ÷ c
= 2^5 - 3(2) + 4(2) ÷ 8
= 32 - 6 + 8 ÷ 8
= 32 - 6 + 1
= 27
Thus, when a = 2, b = 3, and c = 8, the expression evaluates to 27.
Please provide the other expressions to evaluate. that was bot
Apologies for any confusion. Let's re-evaluate the expression using the given values:
a5 - bc + 4a ÷ c
= 2^5 - 3(8) + 4(2) ÷ 8
= 32 - 24 + 8 ÷ 8
= 32 - 24 + 1
= 8 + 1
= 9
Therefore, when a = 2, b = 3, and c = 8, the expression evaluates to 9. that was also bot so which one was it
a5 - bc + 4a ÷ c
= 2^5 - 3(2) + 4(2) ÷ 8
= 32 - 6 + 8 ÷ 8
= 32 - 6 + 1
= 27
Thus, when a = 2, b = 3, and c = 8, the expression evaluates to 27.
Please provide the other expressions to evaluate. that was bot
Apologies for any confusion. Let's re-evaluate the expression using the given values:
a5 - bc + 4a ÷ c
= 2^5 - 3(8) + 4(2) ÷ 8
= 32 - 24 + 8 ÷ 8
= 32 - 24 + 1
= 8 + 1
= 9
Therefore, when a = 2, b = 3, and c = 8, the expression evaluates to 9. that was also bot so which one was it
Apologies for the confusion. Let's re-evaluate the expression again:
a5 - bc + 4a ÷ c
= (2^5) - (3 * 2) + (4 * 2) ÷ 8
= 32 - 6 + 8 ÷ 8
= 32 - 6 + 1
= 26 + 1
= 27
So, when a = 2, b = 3, and c = 8, the expression evaluates to 27.
a5 - bc + 4a ÷ c
= (2^5) - (3 * 2) + (4 * 2) ÷ 8
= 32 - 6 + 8 ÷ 8
= 32 - 6 + 1
= 26 + 1
= 27
So, when a = 2, b = 3, and c = 8, the expression evaluates to 27.